The Role of Artistic Activities in Promoting Health Awareness to Kindergarten Children "Afield Study on Kindergartens in Lattakia City" - صبيرة, فؤاد; سلطان, منال; مصطو, مريانا (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research aim to identify the reality of the Health Awareness of the kindergarten Children through art activities in Lattakia City, and to identify the role of kindergarten Care takers in enhancement the Health Awareness for the Children in Lattakia City through Activities Art. To achieve the object of the research a questionnaire has been included (42) paragraphs, divided into two main axes: (The reality of the Health Awareness of the kindergarten Children through art activities, and the role of kindergarten Care taker in enhancement the Health Awareness for the Children through Activities Art), then applied to a sample of (158) Kindergartens Care takers for the academic year 2018/2019. The present research used the descriptive analytical approach. The research ended up with the following results: The reality of the Health Awareness of the kindergarten Children through art activities in Lattakia city from the view point of the Care takers Kindergartens was middle degree. No statistically significant differences regarding the role of Care takers Kindergartens in enhancement the Health Awareness for the Children through Activities Art in Lattakia city according to variables (experience and training courses). There are statistically significant differences regarding the role of Care takers Kindergartens in enhancement the Health Awareness for the Children through Activities Art in Lattakia city according to variable educational qualification in favor of the Education Preparation Diploma Care takers. The recommendations that are reached through the research results were interesting of the Health education programs at kindergartens stage, also training courses of Care takers in the programs of Health education preparation at teaching the Children.